Development and Characterization of Nifedipine Loaded Liposomal In-Situ Gel For the Effective Of Anal Fissure - Raghav, Prashant; Kumar, Sachin (Journal of Neonatal Surgery, 2025)
The current research intended to improve and evaluate a liposomal in-situ gel formulation for the sustained topical delivery of nifedipine. Preformulation studies confirmed the drug's physicochemical compatibility, solubility, and stability. By using thin film hydration approach nifedipine-loaded liposomes were prepared and evaluation done for entrapment efficiency (82.7± 0.46 %), particle size (180.4 nm), zeta potential (−22.3 mV) and polydispersity index (0.461). The optimized liposome (NL1) was incorporated into a Carbopol 934-based in-situ gel and evaluated for clarity, pH, gelling time, viscosity, drug content, and gelation temperature. In-vitro relief studies presented continued drug delivery up to 96.24% over 24 hours, and release kinetics best fit the Korsmeyer-Peppas model (R² = 0.993), indicating anomalous diffusion. The formulation remained stable over 3 months, suggesting potential for enhanced therapeutic efficacy and patient compliance in topical nifedipine delivery.